2018
DOI: 10.1007/s12034-018-1592-4
|View full text |Cite
|
Sign up to set email alerts
|

Bio-inspired AgNPs, multilayers-reduced graphene oxide and graphite nanocomposite for electrochemical $$\hbox {H}_{2}{\hbox {O}}_{2}$$ H 2 O 2

Abstract: A bio-mediated route for the synthesis of silver nanoparticles (AgNPs) is an area of interest in research of many scientists, and this work aims to study the electrocatalytic activity of these particles during electrochemical sensing of H 2 O 2 in a phosphate buffer media. The composite electrodes were fabricated using nearly spherical AgNPs and reduced graphene oxide (rGO) with the graphite (99.999% purity) support made of graphite paste. Graphene oxide (GO) was first synthesized using the modified Hummers me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…R.K. Das et al had developed a spherical AgNPs and rGO via bio-mediated route and examined for electrochemical sensing of H2O2. An amperometric method detection limit was found at 19.04 μM with high H2O2 concentration [155]. Further, T. Dodevska and coworkers have reported that Rosa damascena waste extracts synthesized AgNPs.…”
Section: Carbon Based Nanomaterials and Its Electrochemical Sensing Applicationsmentioning
confidence: 94%
See 1 more Smart Citation
“…R.K. Das et al had developed a spherical AgNPs and rGO via bio-mediated route and examined for electrochemical sensing of H2O2. An amperometric method detection limit was found at 19.04 μM with high H2O2 concentration [155]. Further, T. Dodevska and coworkers have reported that Rosa damascena waste extracts synthesized AgNPs.…”
Section: Carbon Based Nanomaterials and Its Electrochemical Sensing Applicationsmentioning
confidence: 94%
“…1.3 μA mgdL -1 cm - AgNPs and RGO [150] Justiciaglauca leaf extract DPV 0.836 µA µM -1 cm -2 0.5 to 900 µM 0.261 µM 7.0 nitrobenzene -RGO/Au-NPs [151] Terminalia chebula leaf extract DPV 5.12, 0.28 and 0. [155] Sunlight as the energy Cyclic voltammo gram -1 to 26 nM 1 pM 7.4 Paraoxon -Graphite/rGO /AgNPs [156] Sechiumeduleis an herbaceous perennial climber Amperom etric -1-33mM…”
Section: Lead Poisoning 6 Smentioning
confidence: 99%